Acrometastasis following colorectal cancer: A case report and review of literature. (2016) - Agha, Kozar; Akbari, Khalid; Abbas, Syed Husain; Middleton, Simon; McGrath, Daniel
Highlights: Acrometastasis from colorectal cancer is very rare. Unusually persisting symptoms in hands or feet may be red flags in cancer patients. Early detection and treatment of acrometastasis may improve long-term survival. A multidisciplinary approach should be taken to manage acrometastasis. Abstract: Introduction: Colorectal cancer commonly metastasises to the liver, peritoneum and lungs. Bony metastases are uncommon in colorectal cancer and in particular metastases to the hands or feet (acrometastasis) are an extremely rare occurrence. Case presentation: A 65-year-old male with a colonic malignancy underwent elective anterior resection. Intra-operatively he was found to have a pelvic collection necessitating an end colostomy. Histology confirmed complete Dukes B tumour excision with no evidence of lymph node metastases. The patient underwent chemo-radiotherapy but was unsuitable for reversal of Hartmann's due to elevated CEA levels and asymmetrical thickening of the rectal stump with a solitary lung nodule identified at a one-year surveillance CT. The lung nodule was resected revealing metastatic adenocarcinoma and biopsies from the rectal stump showed chronic inflammatory changes. The patient was offered further chemotherapy. However, six years after his original surgery the patient presented with an acutely painful left foot with radiographic appearances of an infiltrative sclerotic and lucent lesion confirmed as a calcaneal acrometastasis on Magnetic Resonance Imaging (MRI). Discussion: Diagnosis of acrometastasis is challenging and generally constitutes a wider metastatic process with poor prognosis. Patients are often asymptomatic or present with symptoms mimicking benign lesions such as arthritis, infection or ligamentous sprains of the hands or feet. Therefore, there should be a high index of suspicion and prompt radiological investigation is warranted in order to exclude disease recurrence. Conclusion: Although acrometastasis may indicate a poor prognosis, timely diagnosis and intervention may facilitate improvement of long-term survival and symptomatic management.